ANALISIS PENERAPAN ASAS PACTA SUNT SERVANDA DALAM PERJANJIAN YANG TERDAPAT KLAUSULA ARBITRASE APABILA ADANYA GUGATAN KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Darren Andreas; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
The arbitration clause was born from the agreement of the parties in making the agreement and this arbitration clause must be made in writing. With the arbitration clause the parties have agreed that if a dispute arises in the future between the parties, the dispute is resolved through an arbitration institution that has been agreed in the agreement, This is confirmed in Article 3 of the Law on Arbitration and Alternative Dispute Resolution which states that the district court is not authorized to adjudicate disputes between parties that have been bound by an arbitration agreement. However, Article 303 of the Bankruptcy and Suspension of Debt Payment Obligations Law states that a commercial court. So that the problems discussed in this thesis are What is the position of the arbitration clause in event of a bankruptcy lawsuit and delay in debt payment obligations and How is the application of the pacta sunt servanda principle to bankruptcy cases and postponement of debt payment obligations in the arbitration clause. The research method in this thesis uses the method normative research supported by interview data. Data The results showed that although the parties had agreed to resolve their dispute through arbitration, one party more often submitted a dispute to the commercial court.